2011
DOI: 10.1016/j.steroids.2010.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photochemical transformation of 3β,21-dihydroxypregna-5,7-dien-20-one to novel secosteroids that show anti-melanoma activity

Abstract: We have synthesized 3β,21-dihydroxypregna-5,7-dien-20-one (21(OH) 7DHP) and used UVB radiation to induce its photoconversion to analogues of vitamin D (pD), lumisterol (pL) and tachysterol (pT). The number and character of the products and the dynamics of the process were dependent on the UVB dose. The main products: pD and pT compounds were characterized by UV absorption, MS and NMR spectroscopy after RP-HPLC chromatography. In addition, formation of multiple oxidized derivatives of the primary products was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
81
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(86 citation statements)
references
References 53 publications
5
81
0
Order By: Relevance
“…However, the synthetic hydroxyderivative of L3, 1,25-dihydroxy-L3, demonstrates biological activity apparently acting through binding to a second site on the vitamin D receptor (VDR) that mediates nongenomic responses (Dixon et al, 2011; Mizwicki et al, 2004; Rebsamen et al, 2002). Using chemical photosynthesis to generate vitamin D analogs with a short side chain (pD and aD compounds) we also generated pL and hydroxy-pL-derivatives (Zmijewski et al, 2008, 2009, 2011). Initial testing of their biological activity showed that pL inhibited the proliferation and stimulated the differentiation of leukemia cells (Slominski et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the synthetic hydroxyderivative of L3, 1,25-dihydroxy-L3, demonstrates biological activity apparently acting through binding to a second site on the vitamin D receptor (VDR) that mediates nongenomic responses (Dixon et al, 2011; Mizwicki et al, 2004; Rebsamen et al, 2002). Using chemical photosynthesis to generate vitamin D analogs with a short side chain (pD and aD compounds) we also generated pL and hydroxy-pL-derivatives (Zmijewski et al, 2008, 2009, 2011). Initial testing of their biological activity showed that pL inhibited the proliferation and stimulated the differentiation of leukemia cells (Slominski et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Initial testing of their biological activity showed that pL inhibited the proliferation and stimulated the differentiation of leukemia cells (Slominski et al, 2010). Its 21- hydroxyderivative, 3β,21-dihydroxy-9β,10α-pregna-5,7-dien-20-one (21(OH)pL3), also inhibited the proliferation of keratinocytes and melanoma cells, with high potency in the case of melanotic SKMEL-188 melanoma cells (Zmijewski et al, 2011). This steroid also stimulated translocation of a VDR-green-fluorescent-protein construct from the cytoplasm to the nucleus of melanoma cells suggesting that such effects can be mediated by the VDR.…”
Section: Discussionmentioning
confidence: 99%
“…7-DHP is further modified in this pathway by the classical enzymes of steroid metabolism resulting in 5,7-diene-analogues, some of which have been detected in vivo [15, 16]. In vitro studies have shown that these 5,7-dienes can be converted to the corresponding vitamin D analogues following UVB irradiation [911]. Several of these new derivatives, which have a short side chain compared to vitamin D 3 , display biological activity [6, 10, 11, 15, 17].…”
mentioning
confidence: 99%
“…In vitro studies have shown that these 5,7-dienes can be converted to the corresponding vitamin D analogues following UVB irradiation [911]. Several of these new derivatives, which have a short side chain compared to vitamin D 3 , display biological activity [6, 10, 11, 15, 17]. In contrast, CYP11A1 acts directly on vitamin D to produce hydroxyvitamin D derivatives which retain a full-length side chain, with these products being detected both in vitro [1214, 18, 19] and in vivo [20, 21].…”
mentioning
confidence: 99%
See 1 more Smart Citation